Impact of Histological and Endoscopic Remissions on Clinical Recurrence and Recurrence-free Time in Ulcerative Colitis. Issue 12 (December 2017) - Ponte, Ana; Pinho, Rolando; Fernandes, Sónia; Rodrigues, Adélia; Alberto, Luís; Silva, João Carlos; Silva, Joana; Rodrigues, Jaime; Sousa, Mafalda; Silva, Ana Paula; Proença, Luísa; Freitas, Teresa; et al.
Abstract : Background: Clinical and endoscopic remissions constitute the therapeutic goals in ulcerative colitis (UC). Histological healing is currently not a target in UC. This study aims to determine the impact of the definition of endoscopic remission (Mayo endoscopic subscore [MSe] 0–1) and histological activity in the recurrence of UC and recurrence-free survival time. Methods: Patients with UC in clinical remission (partial Mayo score ⩽ 1) and endoscopic remission (MSe ⩽ 1) who underwent colonoscopy with biopsies between March 2010 and December 2013 were included. The validated Nancy score was used to evaluate histological activity, which considers inactivity if 0 to 1 and activity if 2 to 4. The recurrence-free time was evaluated and recurrence was defined as partial Mayo score ≥ 2, therapy to induce remission, hospitalization, or colectomy. Predictive factors associated with recurrence and time to recurrence were determined. Results: Sixty patients were included; 58.3% (n = 35) were women, with a mean age of 52.7 years. MSe = 1 was observed in 46.7% (n = 28) and histological activity in 38.3% (n = 23). Clinical recurrence occurred in 31.7% (n = 19) of patients, with a cumulative risk of 17.1%/24.5%/26.7%/40.1% at 12/24/36/48 months, respectively. MSe = 1 ( P = 0.02) and histological activity ( P = 0.007) were significantly associated with recurrence. Of these, only histological activity ( P = 0.03) was an independent predictive factor of recurrence. Patients with MSe = 1 ( P = 0.02) and with histological activity ( P = 0.01) had a significantly shorter recurrence-free time in univariate analysis. In multivariate analysis, only histological activity ( P = 0.02) was an independent predictive factor of lower recurrence-free time. Conclusion: The presence of histological activity represents an independent predictive factor of recurrence and time to recurrence, which was not verified with MSe 0 to 1. Abstract : Article first published online 6 October 2017.